Cellular senescence induced by cholesterol accumulation is mediated by lysosomal ABCA1 in APOE4 and AD - Shaowei Wang; Boyang Li; Jie Li; Zhiheng Cai; Cristelle Hugo; Yi Sun; Lu Qian; Julia TCW; Helena C. Chui; Dante Dikeman; Isaac Asante; Stan G. Louie; et al. (Molecular Neurodegeneration)
Abstract Background Cellular senescence, a hallmark of aging, has been implicated in Alzheimer’s disease (AD) pathogenesis. Cholesterol accumulation is known to drive cellular senescence; however, its underlying mechanisms are not fully understood. ATP-binding cassette transporter A1 (ABCA1) plays an important role in cholesterol homeostasis, and its expression and trafficking are altered in APOE4 and AD models. However, the role of ABCA1 trafficking in cellular senescence associated with APOE4 and AD remains unclear. Methods We examined the association between cellular senescence and ABCA1 expression in human postmortem brain samples using transcriptomic, histological, and biochemical analyses. Unbiased proteomic screening was performed to identify the proteins that mediate cellular ABCA1 trafficking. We created ABCA1 knock out cell lines and mouse models to validate the role of ABCA1 in cholesterol-induced mTORC1 activation and senescence. Additionally, we used APOE4-TR mice and induced pluripotent stem cell (iPSC) models to explore cholesterol-ABCA1-senescence pathways. Results Transcriptomic profiling of the human dorsolateral prefrontal cortex from the Religious Order Study/Memory Aging Project (ROSMAP) cohort revealed the upregulation of cellular senescence transcriptome signatures in AD, which correlated with ABCA1 expression and oxysterol levels. Immunofluorescence and immunoblotting analyses confirmed increased lipofuscin-stained lipids and ABCA1 expression in AD brains and an association with mTOR phosphorylation. Discovery proteomics identified caveolin-1, a sensor of cellular cholesterol accumulation, as a key promoter of ABCA1 endolysosomal trafficking. Greater caveolin-1 expression was observed in APOE4-TR mouse models and AD human brains. Oxysterol induced mTORC1 activation and senescence were regulated by ABCA1 lysosomal trapping. Treatment of APOE4-TR mice with cyclodextrin reduced brain oxysterol levels, ABCA1 lysosome trapping, mTORC1 activation, and attenuated senescence and neuroinflammation markers. In human iPSC-derived astrocytes, the reduction of cholesterol by cyclodextrin attenuated inflammatory responses. Conclusions Oxysterol accumulation in APOE4 and AD induced ABCA1 and caveolin-1 expression, contributing to lysosomal dysfunction and increased cellular senescence markers. This study provides novel insights into how cholesterol metabolism accelerates features of brain cellular senescence pathway and identifies therapeutic targets to mitigate these processes.